INTERNET ADDICTION AMONG UNDERGRADUTE MEDICAL STUDENTS IN HYDERABAD, PAKISTAN. - Muhammad Ilyas Siddiqui1, Muhammad IrfanNizamani2, Fayaz Ahmed Umrani3, Jawad Ahmed Qadri4, Faiza Memon5, Ibrahim Memon6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
BACKGROUND: Technology evolution and internet availability has brought several innovations in the field of science and technology. With these advances, internet addiction is appeared as serious obsessive conditions that have numerous dreadful effects on human physical and mental health. OBJECTIVE: To determine the level of internet addiction among medical undergraduate students of Isra University, Hyderabad. METHODOLOGY: Cross sectional survey was conducted at the Isra University, Hyderabad from August 2018 to January 2019. All medical (MBBS) undergraduate students of either sex were included. Stratified sampling technique is used for selection of participants. A structured questionnaire for internet addiction was used for collection of participant’s information. One way ANOVA and students t-test was used to analyze the gathered data. RESULTS: Total 263 undergraduate medical students participated in the study. Majority (56.65%) of them were male while over half (51.71%) of them were from age group 21-22 years. Over two-third (85.17%) participants were found to be internet addict. Of these internet addicts, 63.84% were mild or minimal internet addict while 12.05% were severely addict participants. There was a statistically significant difference (p<0.05) was observed between gender, age groups, year of study and current residential status of participants. CONCLUSION: Internet addiction is high prevalent among undergraduate medical students especially those belongs age group (19-20) years and males are mainly addicted to internet.